2021
DOI: 10.3389/fnins.2021.684465
|View full text |Cite
|
Sign up to set email alerts
|

Multiscale Computational Model Reveals Nerve Response in a Mouse Model for Temporal Interference Brain Stimulation

Abstract: There has been a growing interest in the non-invasive stimulation of specific brain tissues, while reducing unintended stimulation in surrounding regions, for the medical treatment of brain disorders. Traditional methods for non-invasive brain stimulation, such as transcranial direct current stimulation (tDCS) or transcranial magnetic stimulation (TMS), can stimulate brain regions, but they also simultaneously stimulate the brain and non-brain regions that lie between the target and the stimulation site of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 54 publications
2
22
0
Order By: Relevance
“…Some subsequent modeling studies, however, explored unrelated mechanisms by which TIS modulates ongoing neural activity in the regime of subthreshold field strength of conventional tACS (Esmaeilpour et al, 2021; Howell and McIntyre, 2020), whereas other studies explored axonal targets that are less relevant for transcranial stimulation (Gomez-Tames et al, 2021; Howell and McIntyre, 2020; Mirzakhalili et al, 2020). The TIS E-fields and their effect on neurons have been analyzed in one dimension (1D), either along the direction of largest modulation depth or in a predetermined direction such as the radial direction of the gray matter or along fiber bundles in the white matter (Esmaeilpour et al, 2021; Gomez-Tames et al, 2021; Grossman et al, 2017; Howell and McIntyre, 2020; Huang and Parra, 2019; Lee et al, 2020, 2022; Mirzakhalili et al, 2020; Rampersad et al, 2019; Song et al, 2021). However, the complex three-dimensional (3D) morphology of cortical neurons could significantly affect activation by exogenous E-fields (Aberra et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Some subsequent modeling studies, however, explored unrelated mechanisms by which TIS modulates ongoing neural activity in the regime of subthreshold field strength of conventional tACS (Esmaeilpour et al, 2021; Howell and McIntyre, 2020), whereas other studies explored axonal targets that are less relevant for transcranial stimulation (Gomez-Tames et al, 2021; Howell and McIntyre, 2020; Mirzakhalili et al, 2020). The TIS E-fields and their effect on neurons have been analyzed in one dimension (1D), either along the direction of largest modulation depth or in a predetermined direction such as the radial direction of the gray matter or along fiber bundles in the white matter (Esmaeilpour et al, 2021; Gomez-Tames et al, 2021; Grossman et al, 2017; Howell and McIntyre, 2020; Huang and Parra, 2019; Lee et al, 2020, 2022; Mirzakhalili et al, 2020; Rampersad et al, 2019; Song et al, 2021). However, the complex three-dimensional (3D) morphology of cortical neurons could significantly affect activation by exogenous E-fields (Aberra et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the current intensity ratio altered the position of responding neurons. The characteristics of an envelope may predict the regions of TI stimulation (Gomez-Tames et al, 2021 ). Multichannel array electrodes for TI stimulation enhance focality and reduce scalp sensation in computational modeling and mouse experiments (Song et al, 2020 ).…”
Section: Temporal Interference Stimulationmentioning
confidence: 99%
“…Conventional noninvasive TES usually generates scalp pain when exposing stimulation and limits the intensity of injection currents (Wu et al, 2021 ). TI stimulation can selectively stimulate specific brain regions, such as cortical and subcortical areas, thus preventing the stimulation of scalp nerves and scalp pain (Gomez-Tames et al, 2021 ). Given that DBS has remarkable therapeutic benefits for the treatment of Parkinson’s disease, tremor, and dystonia (Kringelbach et al, 2007 ), TI stimulation as a noninvasive DBS offers exciting prospects for the treatment of various brain disorders.…”
Section: Temporal Interference Stimulationmentioning
confidence: 99%
“…In contrast to the traditional DBS technique, it is easier to steer the stimulation site with TI-DBS. This can be done by changing the electrode positions or by adjusting the relative amplitudes of the current at the different electrode pairs [9]- [11]. With these degrees of freedom, it it possible to find the optimal electrode position so the electric field is high inside in the region of interest and low outside of it.…”
Section: Introductionmentioning
confidence: 99%
“…It was found in silico and in vivo that increasing the carrier frequency of the TI-signal increases the threshold of the input needed to cause stimulation. Changing the beat frequency did not seem to have an influence on the threshold [2], [11]. To model TI-stimulation, it was found that IF-neurons are not sufficient to reproduce the experimental behaviour on single neuron level [16].…”
Section: Introductionmentioning
confidence: 99%